Implementasi Teknik Kriptografi CAESAR CIPHER Untuk Keamanan Data Informasi Berbasis Android - Fina Triana; Jon Endri; Irma Salamah (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Information data security is an important aspect of exchanging data and information. Data and information security can be done in various ways, including by using the cesarean cipher method in cryptographic techniques. The cesarean cipher method of cryptographic technique is a substitution coding system which is done by replacing each alphabet character with other characters along the 26 alphabet characters so that the coding only occurs in the alphabet itself without any other punctuation. This study proposes a modification to the cesarean cipher technique by adding to the number of characters used, namely 256 characters in the ASCII code. The caesar cipher application or CaesarApp uses the methodology of library study, consultation, application design and application testing. The implementation of the CaesarApp application was created using the open-source Android Studio 3.5 application. The results of tests conducted on the CaesarApp application note that the modification of the caesar cipher with 256 ASCII characters results in a secure information data security application, this application has a deficiency in reading limitations on ASCII characters, so characters cannot be read properly on android users.